Strain Typing of Trichosporon asahii Clinical Isolates by Random Amplification of Polymorphic DNA (RAPD) Analysis - Premamalini, Thayanidhi; Rajyoganandh, Vijayaraman; Vijayakumar, Ramaraj; Veena, Hemanth; Kindo, Anupma Jyoti; Marak, Rungmei SK (Journal of Laboratory Physicians, 2021)
Objective The aim of this study was to identify and isolate Trichosporon asahii (T. asahii) from clinical samples and to assess the genetic relatedness of the most frequently isolated strains of T. asahii using random amplification of polymorphic DNA (RAPD) primers GAC-1 and M13.Methods All the clinical samples that grew Trichosporon species, identified and confirmed by polymerase chain reaction (PCR) using Trichosporon genus-specific primers, were considered for the study. Confirmation of the species T. asahii was carried out by T. asahii-specific PCR. Fingerprinting of the most frequently isolated T. asahii isolates was carried out by RAPD using random primers GAC-1 and M13.Results Among the 72 clinical isolates of Trichosporon sp. confirmed by Trichosporon-specific PCR, 65 were found to be T. asahii as identified by T. asahii-specific PCR. Fingerprinting of the 65 isolates confirmed as T. asahii using GAC-1 RAPD primer yielded 11 different patterns, whereas that of M13 primer produced only 5 patterns. The pattern I was found to be the most predominant type (29.2%) followed by pattern III (16.9%) by GAC-1 primer.Conclusions This study being the first of its kind in India on strain typing of T. asahii isolates by adopting RAPD analysis throws light on genetic diversity among the T. asahii isolates from clinical samples. Fingerprinting by RAPD primer GAC-1 identified more heterogeneity among the T. asahii isolates than M13.
Keywords: strain typing; Trichosporon asahii; genetic diversity; RAPD